Anti-inflammatory and tight junction protective activity of the herbal preparation STW 5-II on mouse intestinal organoids - Elbadawi, Mohamed; Ammar, Ramy M.; Aziz-Kalbhenn, Heba; Rabini, Sabine; Klauck, Sabine; Dawood, Mona; Saeed, Mohamed E M; Kampf, Christopher J.; Efferth, Thomas (Phytomedicine, 2021)
Background - Irritable bowel syndrome (IBS) is a functional bowel disorder, in which recurrent abdominal pain is associated with defecation or a change in bowel habits. STW 5-II is a combination of six medicinal herbs with a clinically proven efficacy in managing IBS. - Aim - This study aims to establish an in vitro IBS model using mouse intestinal organoids and to explore the anti-inflammatory and tight junction protective activities of the multi-herbal preparation STW 5-II. - Methods - Intestinal organoids were cultured in 1:1 Matrigel™ and medium domes. Inflammation and tight junction disruption were induced by a cocktail of cytokines (TNFα, IFNγ, IL-1β, IL-6) and bacterial proteins (LPS, flagellin). Organoids were treated with different concentrations of STW 5-II, and its multi-target activity was assessed using microarray analyses, RT-qPCR, immunofluorescence, western blot, immunohistochemistry, and a FITC permeability assay. In addition, we analyzed the expression of pNF-κB, pSTAT1, iNOS and ZO-1. In silico analyses were conducted to predict and identify the active components that may be responsible in mediating the multi-target anti-inflammatory activity of STW 5-II. - Results - An organoid based IBS model was successfully established. STW 5-II effectively reduced the cytokines-induced overexpression of the pro-inflammatory mediators pNF-κB, pSTAT1 and iNOS. Moreover, STW 5-II attenuated cytokine-mediated downregulation of the tight junction protein, ZO-1. This finding was confirmed by a FITC permeability assay. In silico analyses revealed a promising inhibitory activity of some isolated compounds from STW 5-II against NF-κB, STAT1 and iNOS. - Conclusion - STW 5-II possesses multiple anti-inflammatory as well as tight junction protective activities that could explain its clinically proven efficacy in managing IBS symptoms.
Gesehen am 12.08.2021